VAL IT FRAMEWORK 2.0 : PENILAIAN INVESTASI TEKNOLOGI INFORMASI PADA SEKOLAH TINGGI MULTI MEDIA â€œMMTCâ€ YOGYAKARTA - Kuswantoro, RB. Hendri; Utami, Emma; Amborowati, Armadyah (Universitas Respati Yogyakarta, 2013)
Placement of funds at this time in the hope of future gain is essentially the investment, on the other hand that the output is used by private companies to produce output in the future is called investment. Value of investment based on business valuation means the value of an asset or to specify or memprospektifkan ownership. Type this value into account ownership of the knowledge, skills, expectations of risk and earnings potential, as well as other factors. The benefits of the investment will be felt in the period tertentu.Namun how investment can be measured and the known benefitsare appropriate in pengimplemtasiannya.The concept of Val IT Framework 2.0, which was initiated by the Information Technology Governance Institute (ITGI) (2008), through the experience of a set team of practitioners, academics, and practices, some of the methodologies, and research to develop the Val IT framework. Development of the Val IT framework with several research activities, publications and support services. Val IT consists of a set of basic principles and the three main processes for measuring the value of IT Value Gavenance, Portfolio Managament, Investment Management.Masing these 3 main process then broken down into several sub-items. Through the business case method can provide a complete picture and transparent to the management on the benefits of an investment and helps the management to make decisions on investment, so it can be used as controls achieving the expected value of an investment in Information Technology. Keywords: IT investments, Val IT, Business Case.